Analisis dan Tofografi Komposit Serat Pohon Pisang Sebagai Tiang Rambat Tanaman lada Dengan Metode RSM - yuliyanto yuliyanto (Politeknik Manufaktur Negeri Bangka Belitung, 2019)
Pepper cultivation is now very rare. One reason for this is that wood is not available for the pepper vine. These vines are usually bought or taken from the surrounding forest but now the forest has been turned into oil palm plantations and mining holes. The vine is a patch where the roots of the pepper plant can grow well. This study uses the RSM method with 20 trials of data processing and 6 times of repetition in the middle of the process. This study aims to determine the ability of banana tree fiber-reinforced composites using a polyester matrix BQTN 157 against tensile strength at the beginning of manufacture and 6 months as well as the topography of the composite fracture. The results of Tensile testing at 0 months is in the averaged of 20,595 MPa while in the following 6 months there is a decrease in Tensile strength by an average of 0.478 MPa. It means that tensile strength will decrease when the composite age increases even though the value is small. Data with RSM shows that the F-calculated F value of the model = 14.69 obtained from the significance level of 0.01 or 1%. While the Lack of Fit value that occurs is 0.229 and does not have a major effect.